Demographic and geographic patterns of cetacean-based food product consumption and potential mercury exposure within a Caribbean whaling community. Issue 6 (7th June 2021) - Fielding, Russell; Kiszka, Jeremy J.; Macdonald, Catherine; McCormack, Meaghan A.; Dutton, Jessica; Ollivierre, Alison D.; Arnett, James A.; Elkins, Molly; Darby, Niko A.; Garcia, Hannah-Marie; Skinner, Suzanne; Tucker, Haley; et al.
Abstract: Exposure to mercury (Hg), especially methylmercury (MeHg), through the consumption of seafood is a major public health concern. St. Vincent & the Grenadines (Eastern Caribbean) supports two related whaling operations, which produce food from cetaceans for human consumption. Recent data suggest that Hg concentrations in cetacean tissue samples exceed recommended consumption limits. Our objective was to determine the role of cetacean-based food products in the diet of the Vincentian population as a proxy for exposure to MeHg using interview surveys (n = 921). Based upon provisional tolerable weekly intake (PTWI) guidelines for MeHg from the Food and Agricultural Organization (FAO) and the World Health Organization (WHO), we determined safe weekly consumption amounts for specific cetacean-based food products, based upon reported consumption patterns. We found cetacean-based food products to be included in the diet of 77.4% of respondents. Respondents' gender and geographical home region are the most important factors influencing cetacean consumption. Frequency and amount of consumption vary, but generally exceed calculated safe weekly limits. The consumption of cetacean-based food products may represent a public health risk, as a large portion of the population may be exposed to high MeHg concentrations.